Identitetna koda: pluralnost, binarnost, ničelnost - Polovynkina, Mariia (Slavia Centralis, 2024)
The article studies the identity concept in the novel Flights by Olga Tokarczuk. Plural, binary, and zero identities are considered. The article shows how the concept of identity is manifested in literature, although it also contains elements of philosophy and cultural studies, as they are important for a better understanding of the novel. The connection between binary and plural identities and the individual’s physical or mental “splitting” is shown. Manifestations of zero identity and possible reasons for its formation are discussed. For this type, a feeling of indifference is defined as one of the key factors. The importance of basic oppositions for the forming of one’s own “I” was also determined. A new scheme of identity formation, which is based on the primary need for self-defence, is proposed. Special attention is paid to the novel’s title, its translation options, and its associated concepts. The impact on identity of factors such as attention shift, crisis, desire, change of priorities, revaluation of values, and tendency towards simplification is also demonstrated.
Keywords: identity, Olga Tokarczuk, Flights, Polish literature